Effect of Packaging on Instant Foods from Root Vegetables - Oleg K. Motovilov; Olga V. Golub; Nataliia I. Davydenko; Galina P. Chekryga; Alla G. Stepanova (Техника и технология пищевых производств)
Russian cuisine reflects the identity of its peoples. However, modern nutrition tends to level the multicultural peculiarities of Russian cuisine. This research objective was to identify the effect of packaging and storage time on the quality profile of instant turnip and rutabaga porridges. The study featured quality indicators of food concentrates. Samples of instant porridges were packaged in sachet bags and cups made of complex materials. They were stored at a 20–25°C and a relative humidity of ≤ 75% for 8 months. The sensory, physicochemical, and microbiological variables were measured using standard research methods. After 6 and 8 months of storage, the total sensory assessment for the porridge cups was higher by 1.0 and 2.0 points, respectively, than for the porridge sachets. The cups did not affect the moisture and fat content during storage. The recoverability of the cupped samples was higher by 10.9 and 14.2% after 6 and 8 months of storage, respectively. The mesophilic aerobic and facultative anaerobic microbial count for porridge cups fell by 11.0 times after 6 months of storage and by 3.2 times after 8 months of storage, compared to the sachets. The tests revealed no yeast, mold, Bacillus cereus, coliform bacteria, or pathogenic microorganisms. Shelf-life had a greater effect on quality profile of instant porridge than packaging. In this research, the recommended shelf life for instant turnip and rutabaga porridges was 6 months. The effect of other packaging types and materials on food concentrates is a promising research direction.